Diversidade de Trichoptera Kirby, 1813 em diferentes escalas espaciais da Bacia do Alto Paraguai - Santos, Rogério Conceição Lima dos (2014)
Aquatic Ecosystems are hierarchically organized and incorporate into successive levels different spatial scales, which influence the aquatic communities. The understanding of ecological attributes involved is crucial to prevent the loss of biodiversity and to subsidize conservation strategies. The objectives of this study are to identify which spatial scales are associated with higher beta diversity and what are the environmental factors most important for structuring community of Trichoptera in scales of streams and watersheds. The collections were spatially graded in four scales: conservation Unit (Level 4); 12 watersheds (Scale 3); 36 streams (Level 2); micro-habitats (Scale 1). For sampling we use the manifold Surber sampler (0.250 mm), and the canopy was measured through the Vegetation Index by Difference (NDVI). The relations between the components of diversity were carried out through the analysis of additive partitioning, and the influence of the environment in the community through multiple regression multivariate dimensions of NMDS and PCA axs. Were recorded 4325 Trichoptera larvae, distributed in 36 morphospecies. The families with the highest richness were Hydroptilidae (9 spp.) and Leptoceridae (8 spp.). The additive partitioning demonstrated that the watershed scale are associated with higher beta diversity, both for the metric of wealth (β3 = 25%) and Shannon diversity (β3= 18,25%). The multiple regression analysis multivariate analysis between the axs of the PCA and the dimensions of the NMDS, the watershed scale, demonstrated that the vegetation cover and electrical conductivity were related with abundance (Axis 1 - Pillai Trace=0,58686, F = 5,6820, p = 0,029) and presence and absence (Axis 1 - Pillai Trace= 0,58187, F = 5,5665, p = 0,03) Trichoptera larvae. The community of Trichoptera in different spatial scales (substrates, stream, and watershed conservation unit) was affected by multiple local and regional factors. The largest changes occurred in the scale of watersheds, influenced by heterogeneity of micro-habitats, vegetation coverage, and electrical conductivity.